Both GLS silencing and GLS2 overexpression synergize with oxidative stress against proliferation of glioma cells. - Martín-Rufián, Mercedes; Nascimento-Gomes, Renata; Higuero, Ana; Crisma, Amanda R.; Campos-Sandoval, José A.; Gómez-García, María C.; Cardona, Carolina; Cheng, Tzuling; Lobo, Carolina; Segura-Checa, Juan Antonio; Alonso-Carrión, Francisco José; Szeliga, Monika; et al. (Springer Nature, 2014)
Mitochondrial glutaminase (GA) plays an essential role in cancer cell metabolism, contributing to biosynthesis, bioenergetics, and redox balance. Humans contain several GA isozymes encoded by the GLS and GLS2 genes, but the specific roles of each in cancer metabolism are still unclear. In this study, glioma SFxL and LN229 cells with silenced isoenzyme glutaminase KGA (encoded by GLS) showed lower survival ratios and a reduced GSH-dependent antioxidant capacity. These GLS-silenced cells also demonstrated induction of apoptosis indicated by enhanced annexin V binding capacity and caspase 3 activity. GLS silencing was associated with decreased mitochondrial membrane potential (ΔΨm) (JC-1 dye test), indicating that apoptosis was mediated by mitochondrial dysfunction. Similar observations were made in T98 glioma cells overexpressing glutaminase isoenzyme GAB, encoded by GLS2, though some characteristics (GSH/ GSSG ratio) were different in the differently treated cell lines. Thus, control of GA isoenzyme expression may prove to be a key tool to alter both metabolic and oxidative stress in cancer therapy. Interestingly, reactive oxygen species (ROS) generation by treatment with oxidizing agents: arsenic trioxide or hydrogen peroxide, synergizes with either KGA silencing or GAB overexpression to suppress malignant properties of glioma cells, including the reduction of cellular motility. Of note, negative modulation of GLS isoforms orGAB overexpression evoked lower c-myc and bcl-2 expression, as well as higher pro-apoptotic bid expression. Combination of modulation of GA expression and treatment with oxidizing agents may become a therapeutic strategy for intractable cancers and provides a multi-angle evaluation system for anti-glioma preclinical investigations.
Política de acceso abierto tomada de: https://v2.sherpa.ac.uk/id/publication/8070
Keywords: Glutaminasa; Cáncer - Aspectos moleculares; Apoptosis; Cancer; Glioma; Glutaminase; Glutathione; ROS